Determination of lower order perturbations of the polyharmonic operator from partial boundary data. Issue 11 (1st November 2016) - Ghosh, Tuhin; Krishnan, Venkateswaran P.
Abstract : We consider a perturbed polyharmonic operator of order defined on a bounded simply connected domain with smooth connected boundary of the form: where and stands for the greatest integer function. In the biharmonic case, such operators arise in the study of certain elasticity and buckling problems. We study an inverse problem involving and show that all the coefficients, and can be recovered from partial Dirichlet-to-Neumann (D-N) data on the boundary.